Analisis Framing Media Indonesia.com dan Detik.com Dalam Isu Endorse Jokowi Pada Prabowo Subianto - Yaqin M.S, Agus Ainul (Program Studi Ilmu Komunikasi, 2023)
The mainstream media in constructing news is always different. Construction depends on a variety of influencing factors, such as political interests, socio-cultural economy and ideology. In this study, researchers examined "Framing Analysis of Media News Indonesia.com and Detik.com in the issue of Jokowi's endorsement of Prabowo Subianto. The research uses a qualitative approach with a descriptive type of research. The analysis method is the framing analysis of the Robet N.Entman model. The result of the study is the difference in framing Detik.com and MediaIndonesia in the issue ofJokowi's endorsement of Prabowo Subianto. Keywords: Social Construction, Endorse, Jokowi, Prabowo Subianto